ANALYSIS OF FACTOR FACTORS THAT INFLUENCE DIVIDEND POLICY IN CONSUMPTION GOODS COMPANY LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2015-2017 - Mendrofa, Arisman; Rajagukguk, Tiara Devi; Nababan, Renni Erawati; Silalahi, Jen Meilan; Aruan, Deasy Arisandy (2020)
This study aims to determine the factors that influence dividend policy in consumer goods industry companies. The research method used is quantitative. This type of quantitative descriptive research is based on a population level of 50 companies and a sample of 20 companies in the 2015-2017 period with a purposive sampling technique. Data collection techniques by means of documentation and secondary data sources from the IDX financial statements for the 2015-2017 period. This research was tested using a classic assumption test. The results of the analysis of the coefficient of determination obtained an adjusted R square value of 0.376 means that the variation in stock price variables can be explained by variations in the Profitability, Leverage, Liquidity, Capital Structure and Dividend Policy variable is 37.6% while the remaining 62.4% is a variable variation which is not explained in this study. The results showed that partially Profitability has a positive and significant effect on Dividend Policy. While other variables, namely: Leverage, Liquidity, Capital Structure have no effect and are not significant on Dividend Policy.